تقريب دوال فضاء موري على منحنيات ديني الملساء (Latakia University Journal -Basic Sciences Series, 2017)
درسنا في هذا البحث تقريب دوال فضاء موري حيث و إلى دوال كسرية، وذلك على أسرة واسعة من المنحنيات تدعى منحنيات ديني – الملساء. وعلاوة على ذلك، قمنا بتقريب دوال فضاء سميرنوف موري المعرفة على منطقة محاطة بمنحنٍ ينتمي إلى أسرة منحنيات ديني الملساء بكثيرات حدود.In this work, we have studied the issue of approximation of functions from Morrey space ; by rational functions on a large group of curves, which called Dini-smooth curves. Moreover, approximation of functions from Morrey Smirnov space defined on a finite domain with a boundary belonging to Dini- smooth curves by polynomials is obtained.